Measuring cardiomyocyte cellular characteristics in cardiac hypertrophy using diffusion-weighted MRI - Farzi, M; Coveney, S; Afzali, M; Zdora, M-C; Lygate, CA; Rau, C; Frangi, AF; Dall'Armellina, E; Teh, I; Schneider, JE (Wiley, 2023)
Purpose: This paper presents a hierarchical modeling approach for estimatingcardiomyocyte major and minor diameters and intracellular volume fraction(ICV) using diffusion-weighted MRI (DWI) data in ex vivo mouse hearts. Methods: DWI data were acquired on two healthy controls and two hearts3 weeks post transverse aortic constriction (TAC) using a bespoke diffusionscheme with multiple diffusion times (Δ), q-shells and diffusion encodingdirections. Firstly, a bi-exponential tensor model was fitted separately at eachdiffusion time to disentangle the dependence on diffusion times from diffu-sion weightings, that is, b-values. The slow-diffusing component was attributedto the restricted diffusion inside cardiomyocytes. ICV was then extrapolated atΔ=0 using linear regression. Secondly, given the secondary and the tertiarydiffusion eigenvalue measurements for the slow-diffusing component obtainedat different diffusion times, major and minor diameters were estimated assum-ing a cylinder model with an elliptical cross-section (ECS). High-resolutionthree-dimensional synchrotron X-ray imaging (SRI) data from the same speci-men was utilized to evaluate the biophysical parameters. Results: Estimated parameters using DWI data were (control 1/control 2 vs.TAC 1/TAC 2): major diameter—17.4𝜇m/18.0𝜇m versus 19.2𝜇m/19.0𝜇m;minor diameter—10.2𝜇m/9.4𝜇m versus 12.8𝜇m/13.4𝜇m; and ICV—62%/62%versus 68%/47%. These findings were consistent with SRI measurements. Conclusion: The proposed method allowed for accurate estimation of biophys-ical parameters suggesting cardiomyocyte diameters as sensitive biomarkers ofhypertrophy in the heart.